Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1108/ijoa-08-2019-1848
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and spirituality: a mixed methods exploration of executive stress

Abstract: Purpose The purpose of this mixed methods research study was to explore the relationships between spirituality, leader resiliency and life satisfaction/well-being. Design/methodology/approach Using an explanatory sequential design, the authors tested three research hypotheses to explore the relationships between the participants’ spiritual practices and level of resiliency, life satisfaction and sense of well-being. Data were collected from 101 executive MBA alumni of a US-based university. Following the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 51 publications
1
27
0
1
Order By: Relevance
“…Beside rational things, business resilience can be leveraged by intensifying workplace spirituality as an irrational approach. It supports the previous studies (Shelton, Hein, & Phipps, 2019;Esievo, Oshi, Hettey, &Tende, 2019), Although it is perceived as indirect and illogical, this study proved that spiritual activities at workplace can affect directly, positively, and significantly on business resilience. For further elaboration, the research model is extended by adding more other relationships among variables.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Beside rational things, business resilience can be leveraged by intensifying workplace spirituality as an irrational approach. It supports the previous studies (Shelton, Hein, & Phipps, 2019;Esievo, Oshi, Hettey, &Tende, 2019), Although it is perceived as indirect and illogical, this study proved that spiritual activities at workplace can affect directly, positively, and significantly on business resilience. For further elaboration, the research model is extended by adding more other relationships among variables.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have proved that there is a relationship between spirituality and resilience. Shelton, Hein, and Phipps (2019) concluded that people who are involved in meditative practices as spirituality development had a significantly better resilience score than non-meditators. Esievo, Oshi, Hettey, and Tende (2019) found a strong positive correlation between organizational resilience and workplace spirituality.…”
Section: Workplace Spiritualitymentioning
confidence: 99%
“…As stated previously, research highlighted the positive role of workplace spirituality in the promotion of employee well-being [34][35][36][59][60][61]. However, very few studies considered its effects on burnout [41,42,[62][63][64][65].…”
Section: Studymentioning
confidence: 99%
“…The main cause of this burnout is occupational stress. Managers often face a high level of stress in the workplace (Sharma and Cooper, 2016;Shelton et al, 2019;Petru and Jarosova, 2019;Debus et al, 2019;Gilbert et al, 2019;Guedes et al, 2017),which is likely to drain their energy, weakening them psychologically and putting them at risk of burnout (Sahu and Yadav, 2013;Sharma and Cooper, 2016).…”
Section: Introductionmentioning
confidence: 99%